Vibrations of fractional half- and single-degree of freedom systems - Ciaschetti, Valentina; Elishakoff, Isaac; Marzani, Alessandro (Vietnam Journal of Mechanics, 2017)
In this paper we study vibrations of fractional oscillators by two methods: the triangular strip matrix approach, based on the Grunwald-Letnikov discretization of the fractional term, and the state variable analysis, which is suitable for systems with fractional derivatives of rational order. Some examples are solved in order to compare the two approaches and to conduct comparison with benchmark problems.